“Immunity-to-Change Language Technology”: An Educational Tool for Pastoral Leadership Education - Ste-Marie, Lorraine (Teaching theology and religion, 2008)
One of the primary aims of pastoral leadership education is to offer reflective processes that enable learners to surface, critique, and construct different epistemological conceptions of reality leading to more effective pastoral practice. In many pastoral leadership education programs, this type of intentional reflection usually takes place in a mentoring or supervisory relationship as well as in a reflective seminar. In this essay, I describe how I have used the “immunity-to-change language technology” as one type of reflective process for intentional reflection and transformational learning in pastoral leadership education. The results of my research and ongoing use of this educational tool indicate that it can be valuable for enabling change by helping learners expand their pastoral leadership capacities and become more effective in their practice. Given my findings, I conclude that this educational tool could be of interest to other educators who are seeking to broaden their own repertoire of approaches to transformational learning. A version of this research appears in a forthcoming book by the same author, published by Novalis, in Fall 2008.